Estudio de riesgos mecánicos en la empresa industria metálica Cotopaxi - Salgado Molina, Santiago Paúl (2019)
The present research project is about the study "Study of risk mechanics in the company industries metal COTOPAXI" which aim to establish mechanical risk factors in accidents of workers in the company BMI the city of Latacunga. Having the personnel that work in it, indirect beneficiaries direct beneficiaries: are the children of the staff working in the company, customers, who receive the services and suppliers of the company. By means of gathering information on the factors of risk using NTP:330 check questionnaire is has been observed that it is assessed as deficient, upgradeable, acceptable, therefore the only way to reduce the risk factors is of reduce the level of deficiency in the habits of work, management tools, handling equipment, personal protection, physical distribution of enterprise equipment, movement from one place to another, the research methodology was based on the bibliographical method, documentary, observation and field, for the collection of information was used the survey applied to the employees of the company. It is given to the foregoing recommendations as an excellent adecuacion of the physical space of the company, training, signage, delimitation and a good use of the personal protection with suggestions of plans. Tags: training, distribution, delimitation, company, poor, room for improvement, acceptable.